Glucocorticoids influence on rat hematological parameters and catalase activity - Herenda, Safija; Carev, Ivana; Haskovic, Denis; Prevljak, Sabina; Causevic, Sara; Haskovic, Edhem (Frontiers in Pharmacology, 2024)
In this study, the impact of glucocorticoid, betamethasone dipropionate on enzyme activity in vitro and its effects on hematological parameters in vivo was investigated. The immobilized catalase, crucial for cell oxidative stress response via hydrogen peroxide reduction, exhibited a robust electrocatalytic response, maintaining its biological activity. The in vitro inhibition kinetics of catalase, as determined by electrocatalytic methods and expressed using Lineweaver-Burke diagrams, revealed an uncompetitive type of inhibition with altered Imax and Km in the presence of a range of betamethasone dipropionate concentrations. The in vivo experiments conducted on Rattus norvegicus demonstrated significant alterations in hematological parameters following betamethasone dipropionate administration. These changes included a decrease in erythrocyte count, an increase in hemoglobin, a reduction in mean corpuscular volume (MCV), and an elevation in mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC). Notably, the leukocyte counts substantially increased. The observed hematological shifts suggest an impact of betamethasone dipropionate on the hematopoietic system, reinforcing the need for cautious corticosteroid administration. The findings underline the necessity for judicious corticosteroid treatment, acknowledging both enzymatic and systemic repercussions.